Carboxymethylcellulose reinforced starch films and rapid detection of spoiled beverages - Qin, Shijiao; Sun, Hao; Wan, Xiaoli; Wu, Yujia; Lin, Xu; Kan, Huan; Hou, Defa; Zheng, Zhifeng; He, Xiahong; Liu, Can (Frontiers in Bioengineering and Biotechnology, 2023)
The integrity of the packaging of a liquid foodstuff makes it difficult to detect spoilage. Therefore, it is important to develop a sensitive, fast and real-time material for liquid food detection. CMC, as lignocellulose derivatives and starch are widely used in the food industry. In this study, starch films with pH-responsive properties are successfully prepared from full-component starch and corn amylopectin (CA) by adding CMC. The effects of CMC on the mechanical properties, morphology characteristics, physical and chemical structures, stability and pH responsiveness of the starch films are analyzed. The starch/CMC-1.0 composite films display good electrical conductivity and reduce the resistance of the composite film by two orders of magnitude. The composite films have pH response ability; in the simulation of orange juice spoilage experiment, the CA/CMC composite film has a more sensitive current response and was more suitable for the application to liquid food quality detection. Additionally, the starch/CMC composite films have potential applications for rapid detection and real-time monitoring of the safety of liquid food.